Is Cerebral Palsy Changing in High Resource Settings? Data From the Quebec Cerebral Palsy Registry. (September 2019) - Hadjinicolaou, Aristides; Ng, Pamela; PhD, Xun Zhang; Koclas, Louise; Lamarre, Céline; Malouin, Francine; Pigeon, Nicole; Richards, Carol L.; Shevell, Michael; Oskoui, Maryam
Advances in maternal and perinatal care in developed countries have led to improved health outcomes for children. These changes may have impacted the profile of children with a cerebral palsy (CP) and groups at risk for CP over time. Using data from the Canadian CP Registry, the objectives of this retrospective cohort study were to describe the profile of children with CP in Quebec born between 1999 and 2010 and identify possible temporal variation in CP risk factors and phenotypic profile. Our sample consisted of 662 children with CP in Quebec. No change in profile or associated risk factors was observed across the birth cohorts 1999 to 2010. Prematurity remains the largest risk factor for CP in Quebec, and children with CP have multiple comorbidities that contribute to overall CP burden. CP registries offer a unique platform to study spectrum disorders and their longitudinal changes over time.